Cultivating crayfish (Procambarus clarkii) significantly enhances the quantity and diversity of soil microorganisms: evidence from the comparison of rice-wheat and rice-crayfish rotation models - Xu, Hui; Wang, Dan; Li, Xuguang; Li, Jiajia; Xu, Yu; Xu, Zhiqiang (Frontiers in Microbiology, 2025)
Integrated farming of rice (IFA), as a time-honored agricultural model, can effectively increase agricultural productivity and provide ecological benefits. Rice-wheat rotation and rice-crayfish (Procambarus clarkii) rotation are two most widely applied IFA patterns in China. In this study, we compared the differences in soil microbial communities and predicted their functions in these two IFA models by sequencing the 16s rRNA and analyzing the bioinformation. The results showed that crayfish farming effectively increased the abundance and diversity of soil microorganisms. The main differentially abundant phyla between the two groups were Actinobacteriota, Bacteroidota, and Desulfobacterota, while the main differentially abundant genera were Bacteroidetes_vadinHA17, Sphingomonas, and Thiobacillus. The Similarity Percentages (SIMPER) analysis indicated that these species also had the highest contribution to the differences in microbial composition between the two groups. Random forest prediction analysis was employed to identify potential biomarkers to distinguish the two microbial communities. Actinobacteriota, Desulfobacterota, and Spirochaetota were identified as potential biomarker phyla. Streptomyces, Kribbella, and Paludibacter could serve as potential biomarker genera. Functional Annotation of Prokaryotic Taxa (FAPROTAX) analysis revealed that the dominant bacterial functions in the rice-wheat rotation model were aerobic chemoheterotrophy and chemoheterotrophy. In contrast, the bacterial functions in the rice-crayfish rotation model were more diverse, primarily including methylotrophy, human pathogens all and methanotrophy. The results of co-occurrence network analysis showed that crayfish farming enhanced the modularity of the soil microbial community, and revealed that the microbial network in rice-wheat soil had fewer nodes and more edges, which implying more internal connections. In conclusion, the wheat planting and crayfish farming drove significant differences in the soil microbial communities of paddy fields, with Actinobacteriota and Desulfobacterota identified as potential biomarkers. Compared to wheat cultivation, the rotation system incorporating crayfish farming enhanced the richness and diversity of soil microbial species and functions, increased the modularity of the microbial community, and promoted the presence of keystone species with connecting roles. Our study would not only clarify the effects of different IFA models on soil microbial communities, and should also provide valuable insights for future adjusting cropping patterns and controlling current soil microbial ecological problems.